Is male rhesus macaque red color ornamentation attractive to females? - William Allen (Behavioral Ecology and Sociobiology, 2014)
Male sexually selected traits can evolve through different mechanisms: conspicuous and colorful ornaments usually evolve through intersexual selection, while weapons usually evolve through intra-sexual selection. Male ornaments are rare among mammals in comparison to birds, leading to the notion that female mate choice generally plays little role in trait evolution in this taxon. Supporting this view, when ornaments are present in mammals, they typically indicate social status and are products of male-male competition. This general mammalian pattern, however, may not apply to rhesus macaques (Macaca mulatta). Males of this species display conspicuous skin coloration, but this expression is not correlated to dominance rank and is therefore unlikely to have evolved due to male-male competition. Here, we investigate whether male color expression influences female proceptivity toward males in the Cayo Santiago free-ranging rhesus macaque population. We collected face images of 24 adult males varying in dominance rank and age at the peak of the mating season and modeled these to rhesus macaque visual perception. We also recorded female sociosexual behaviors toward these males. Results show that dark red males received more sexual solicitations, by more females, than pale pink ones. Together with previous results, our study suggests that male color ornaments are more likely to be a product of inter- rather than intra-sexual selection. This may especially be the case in rhesus macaques due to the particular characteristics of male-male competition in this species.